Organizacja i działalność prowincjonalnych zakładów dla obłąkanych na Śląsku w latach 1875–1893 - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The organization and the treatment of the mentally ill, presented in this publication, confined to the institutions which were managed by provincial government, which was the most important organ of the provincial parliament Provinzial-Landtag. This publication presents the situation of institutions for the insane, which were created after the establishment of the Second German Empire in 1871. The result of this event was the administrative reform of the 1870s. It was carried out also at the provincial level, that is why institutions for the insane, which since the mid-1820s were part of the assets of the local government, entered into a new organizational forms. Until then they had been managed by special, separate committees for each institution. From then on, on the basis of the provincial ordination of 1875, they were to be subject to the central constituencies in the province of Silesia. There was a national administrator starosta and provincial department Provinzial-Ausschuß, and these modern executive bodies improved the activities of therapeutics for the mentally ill. One should remember the importance of psychiatry in Silesia, where Wroclaw School of Carl Wernicke was established in this period, from which the whole modern psychiatry emerged, and the heads of hospital departments and the doctors of psychiatric hospitals were the most important psychiatrists who influenced the science to the present times eg Clemens Neisser, Emil Kraepelin, Emil Sioli, Ewald Hecker, Carl Kahlbaum and Alois Alzheimer. Upper time limit of this publication is related to the organizational changes, when all provincial institutions for the insane were standardized.
Keywords: Śląsk w XIX wieku; samorząd wojewódzki; organizacja i leczenie osób chorych psychicznie